A case of thrombotic thrombocytopenic purpura related to brucellosis - Balta, S.; Uslu, F.; Ekinci, O.; Merter, M. (Pergamon-Elsevier Science Ltd, 2019)
[Abstract Not Available]
10th Eurasian Hematology Oncology Congress -- OCT 08-11, 2019 -- Istanbul, TURKEY